Implementasi Algoritme Genetika dan Analytical Hierarchy Process untuk Penerimaan Siswa Baru pada Sekolah Menengah Kejuruan - Mala Nurhidayati; Dian Eka Ratnawati; Yuita Arum Sari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Vocational high schools aim to produce qualified graduates in their expertise and skills in each majors. In the process of getting qualified graduates, it takes an initial step, namely selecting new students. The selection process is carried out by considering the value of the Indonesian National Examination, the value of the English National Examination, the value of the National Mathematics Examination, and the National Examination Science score. The methods used to solving this problem are Analytical Hierarchy Process (AHP) and Genetic Algorithms. Individuals in the Genetic Algorithm method are 6 genes. In the initial individuals formed the reproduction process namely crossover and mutation. The last process in this reasearch is the calculation of fitness value. This process resolved by calculating the results of accuracy. The results of the fitness value obtained the largest to the smallest fitness value. From research conducted the output is passing or not passing from prospective students in a predetermined majors. The average accuracy of the combination of the AHP method and the genetic algorithm is 86.85% and the accuracy is obtained using the AHP method is only 76.52%. Based on these results it can be concluded that the merger of AHP methods and genetic algorithms can solve the problem of new student admission at vocational high schools.